The role of environmental management accounting and environmental knowledge management practices influence on environmental performance: mediated-moderated model - Bresciani, Stefano; Ur Rehman, Shafique; Giovando, Guido; Alam, Gazi Mahabubul (Emerald, 2022)
Purpose: This study aims to observe the influence of environmental management accounting (EMA) and environmental knowledge management (KM) practices on environmental performance with mediating role of top management support (TMS). Moreover, green work climate perception (GWCP) is used as a moderator between TMS and environmental performance. Design/methodology/approach: Partial least square-structural equation modeling is used to test research hypotheses. Data was collected to distribute questionnaires in light of the purposive sampling technique; a total of 329 questionnaires were used for final analysis. This study is correlational and cross-sectional. Multiple regression analysis was used to see the influence of EMA, environmental KM practices, TMS and GWCP on environmental performance. Findings: The results reveal that EMA, environmental KM practices and TMS are positively related to environmental performance. Moreover, TMS significantly mediates between EMA, environmental KM practices and environmental performance. GWCP is positively associated with environmental performance. Finally, GWCP significantly strengthens the positive relationship between TMS and environmental performance. Practical implications: This study highlighted a significant issue that of how top management uses EMA, environmental KM practices, TMS and GWCP in examining environmental performance. Moreover, this study covers the gap and supports top management to concentrate on exogenous variables to examine environmental performance. Originality/value: This study adds value to literature to focus on factors that influence environmental performance. This initial research observes the influence of EMA and environmental KM practices on environmental performance with TMS as a mediator in light of the knowledge-based view. Besides, GWCP is used as a moderator between TMS and environmental performance. Finally, our research can provide benefits to researchers, students and managers.